A modified droplet vitrification method for cryopreservation of shoot tips from in vitro potato plants - T. A. Gavrilenko; N. A. Shvachko; N. N. Volkova; Yu. V. Ukhatova (Вавиловский журнал генетики и селекции)
Collections of common potato maintained in the field genebanks suffer significant losses due to the impact of extreme environmental factors, diseases and pests. The solution of the problem of safe long-term preservation of common potato accessions is to create doublet in vitro and cryo-collections. Cryogenic collections are stored at ultra-low temperatures in cryobanks. Several methods of potato cryoconservation are known, of which the droplet vitrification method developed by B. Panis with colleagues in 2005 is the most widely used in genebanks. This paper provides a detailed description of the modified method of droplet vitrification, which is used for cryopreservation of apexes (shoot tips) of potato in vitro plants at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). The method modified at VIR includes the main steps of the original droplet-vitrification method developed by B. Panis and colleagues: 1) preparation of plant material, 2) isolation of shoot tips, 3) treatment of explants with cryoprotector solutions, 4) freezing/immersion in liquid nitrogen, 5) thawing, 6) post-cryogenic recovery and evaluation of viability and regeneration capacity. The modifications of stages 1, 2 and 6 proposed at VIR lead to a significant reduction in the duration of cryopreservation experiments in comparison with the original method of B. Panis. This paper presents the results of cryopreservation of modern potato cultivars and South American landraces which were obtained using the method of droplet vitrification as modified at VIR. The majority (76.7 %) of the studied accessions of cultivated potato were characterized by high rates of postcryogenic recovery (40–95 %) and 23.3 % of the samples had the values of postcryogenic regeneration from 20 to 39 %, which corresponds to the minimal permissible values for long-term storage in a cryobank. Currently the modified droplet-vitrification method is used for further expanding of the VIR potato cryocollection.